Peculiarities of the Modern State of the System of Economic Education in Ukraine - Kateryna Binytska; Dmytro Nikitenko (Pedagogical Discourse, 2014)
The article deals with the study of the problem of the modern state, factors of popularity and perspectives of development of higher economic education in Ukraine. The views of domestic scientific workers as for the problem of development of the system of economic education in modern Ukraine have been analyzed. On the basis of the analysis of domestic theoretical literature the terms, system of economic education, have been determined. The attention is accentuated on the strategic priorities of national system of economic education. Negative features, which are inherent in the modern Ukrainian system of economic education, have been determined. The program for improvement of the modern state of economic education in Ukraine has been elucidated. The views of the modern scientists-economists concerning strategic priorities of the national system of economic education have been offered. The state of modern economic education in Ukraine has been cleared up. It is stipulated by the necessity of transition to the new base of forming and development economic knowledge, which is grounded on spiritual-moral and historic-cultural traditions of Ukrainian society. It is clarified that economic education is oriented to the deepened analysis of economic processes, which assist forming of the bases of socially oriented economy. It is determined that education is the motive power, which changes society, and economic education – is an important factor of social-economic development of the state.